Delayed onset pulmonary glue emboli in a ventilated patient: a rare complication following endoscopic cyanoacrylate injection for gastric variceal haemorrhage. (15th October 2014) - Chew, Joyce Ruo Yi; Balan, Anu; Griffiths, William; Herre, Jurgen
Abstract : Cyanoacrylate injection is a recognised endoscopic treatment option for variceal haemorrhage. We describe a 34-year old man with hepatitis B cirrhosis who presented to the hospital with upper gastrointestinal haemorrhage from gastric and oesophageal varices. Haemostasis was achieved via cyanoacrylate injection sclerotherapy and banding. Ten days later, the patient developed acute hypoxia and fever. His chest radiograph showed wide-spread pulmonary shadowing. A non-contrast CT scan confirmed multiple emboli of injected glue material from the varix with parenchymal changes either suggesting acute lung injury or pulmonary oedema. He gradually recovered with supportive treatment and was discharged home. On follow-up, he remained asymptomatic from a chest perspective. This case report discusses the rare complication of pulmonary embolisation of cyanoacrylate glue from variceal injection sites and the diagnostic dilemmas involved. Emphasis is placed on the importance of maintaining high index of clinical suspicion when assessing patients with possible procedure related complications.